A heart for home - Snelling, Lauraine (Minneapolis, Minn. : Bethany House, 2011)
Astrid and Joshua discover God's plans for them through difficult circumstances in the conclusion to this prairie romance series set in South Dakota.
Keywords: Indian reservations -- Fiction; South Dakota -- Fiction; Christian fiction; Love stories; Historical fiction